Biological role of GITR/GITRL in attributes and immune responses of macrophage. Issue 2 (13th December 2019) - Fu, Zhuo; Wang, Shuang; Li, Jinhua; Zhang, Yunfeng; Li, Han; Li, Guangquan; Wan, Xue; Zhang, Yu
Abstract: Glucocorticoid-induced tumor necrosis factor receptor family-related protein ligand (GITRL), a member of the tumor necrosis factor superfamily, is expressed in APCs and acts as a costimulatory molecule in the immune system. Although the glucocorticoid-induced tumor necrosis factor receptor-related protein (GITR)/GITRL system has been modulated to promote or decrease T cell-related responses in multiple diseases, studies in macrophages are limited. To address this issue, we compared the expression of GITRL in various types of macrophages and analyzed whether GITRL can affect the fundamental properties and major functions of these cells. Our results demonstrated that M1 polarized macrophages had the highest GITRL levels. Furthermore, GITRL overexpression skewed macrophage polarization toward the M1 phenotype, accelerating proliferation and migration and regulating phagocytosis and killing function. Moreover, GITRL-silenced cells showed a loss of these functions, further confirming its vital role. We also developed an acute peritonitis mouse model, in which macrophages were driven to differentiate into a proinflammatory phenotype with GITRL up-regulation, triggering a positive feedback loop. Our results provide molecular insight into how the GITR/GITRL system modulates innate immune responses, suggesting that manipulation of the GITR/GITRL system to treat diseases depends not only on T cell regulation but also on macrophage participation.